Penerapan Practical Experience untuk Memperkenalkan Sains pada Lingkungan SD Negeri Jember Lor 01 Jember - Rahma Rei Sakura; Hery Indria Dwi Puspita; Rudianto Rudianto; Wazirotus Sakinah; Pratama Yuli Arianto (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Science is a system obtained through the scientific method of research. The application of scientific knowledge can be found in various fields such as agriculture, medicine, pharmacy, and technology. The development of scientific knowledge in various fields is the role of the academic community. Community service is one of the three main duties of higher education institutions. Community service activities are carried out by conducting visits to Jember Lor 01 Public Elementary School in order to enhance young generations' knowledge of science through primary schools. The method used in community service is practice experience, which is a learning process that provides practical experiences to facilitate students' understanding of the subject matter. The practices conducted include telekinetic and lava lamp experiments using easily accessible materials. The practices are done in groups and accompanied by one person from the community service team. Based on the enthusiasm of the participants, this activity has been very beneficial in increasing the interest in learning about science from an early age. The synchronization of this community service activity with the natural science subjects is necessary to help students understand the theoretical lessons taught by teachers.